The Effect Of Local Wisdom And Human Resource Competence on The Profit Performance of Box Courier MSMEs In Mataram City - Pieter Umbu Resi Ndapamede (Jurnal Riset Mahasiswa Akuntansi, 2026)
Many UMKM experience weaknesses in business management capabilities, and the quality of their human resources (SDM) remains limited. Local wisdom in the form of cultural values, customs, and practices has the potential to develop into social capital that can enhance the sustainability and business management of UMKM. Based on this phenomenon, this study aims to examine the effect of local wisdom and SDM competence on the profit performance of box courier UMKM in Mataram City. The research employs a quantitative associative approach. The results indicate that local wisdom and SDM competence have no significant effect, either simultaneously or partially, on the profit performance of box courier UMKM in Mataram City. This condition occurs because box courier businesses are classified as micro-scale UMKM, in which profit performance is more sensitive to technical and operational factors than to non-financial factors such as local wisdom. Similarly, with regard to SDM competence, the relatively small number of workers and the simple division of tasks mean that improvements in individual competence are not always followed by increased revenue productivity in micro-scale UMKM. The conclusion of this study is that the profit performance of box courier UMKM in Mataram City is more strongly influenced by technical and financial factors than by non-financial factors such as local wisdom and SDM competence.